라만 분광법을 이용한 반도체 공정 중 표면 분석 - 최태민(Tae Min Choi); 유진욱(JinUk Yoo); 정은수(Eun Su Jung); 이채연(Chae Yeon Lee); 이화림(Hwa Rim Lee); 김동현(Dong Hyun Kim); 표성규(Sung Gyu Pyo) (Biuletyn Uniejowski, 2024)
This article provides an overview of Raman spectroscopy and its practical applications for surface analysis of semiconductor processes including real-time monitoring. Raman spectroscopy is a technique that uses the inelastic scattering of light to provide information on molecular structure and vibrations. Since its inception in 1928, Raman spectroscopy has undergone continuous development, and with the advent of SERS(Surface Enhanced Raman Spectroscopy), TERS(Tip Enhanced Raman Spectroscopy), and confocal Raman spectroscopy, it has proven to be highly advantageous in nano-scale analysis due to its high resolution, high sensitivity, and non-destructive nature. In the field of semiconductor processing, Raman spectroscopy is particularly useful for substrate stress and interface characterization, quality analysis of thin films, elucidation of etching process mechanisms, and detection of residues.